Black soldier fly, Hermetia illucens (L.) (Diptera: Stratiomyidae), and house fly, Musca domestica L. (Diptera: Muscidae), larvae reduce livestock manure and possibly associated nutrients: An assessment at two scales. (1st August 2021) - Miranda, Chelsea D.; Crippen, Tawni L.; Cammack, Jonathan A.; Tomberlin, Jeffery K.
Abstract: The industrial production of insects for waste management or as a protein source is becoming vital to our society. Large volumes of manure are produced by concentrated animal facilities around the globe that must be managed, utilized, and disposed of properly. Flies offer a partial solution with their abilities to reduce these wastes and heavy metal pollutants. Meat and crop proteins are being supplemented by insect proteins for many feeds across the globe, yet science-based studies behind the mass-rearing of insects are still in their infancy. In the current study, the percent change in the composition of nutrients, heavy metals, and fiber, in dairy, poultry, and swine manure degraded by either black soldier fly (BSF) or house fly (HF) larvae was explored. Pre-digested and post-digested manure samples were collected from four independent studies that differed in production scale (number of larvae and feeding regimen): 1) BSF small-scale (100 larvae fed incrementally), 2) HF small-scale (100 larvae fed incrementally), 3) BSF large-scale (10, 000 larvae fed a single time), and 4) HF large-scale (4, 000 larvae fed a single time). Results indicate that nitrogen is a key nutrient impacted by larval digestion of manure by both species, regardless of scale. However, scale significantly impacted reductions of other nutrients, as did the type of manure in which the insects were reared. Ultimately, this study demonstrated that manure type and rearing scale impact the ability of BSF and HF larvae to reduce nutrients and heavy metals in manure, and thus insect management procedures need to be congruent with production emphases of the insects for waste management or protein products. Failure to take scale into consideration could lead to inaccurate assumptions related to industrialized efforts on this topic. Graphical abstract: Image 1 Highlights: Sustainable methods for recycling animal waste are needed to protect the environment. Black soldier fly and house fly larvae can efficiently and effectively manage livestock manure to produce feed and compost. The extent of biodegradation into nutrients, heavy metals and fiber is governed by insect rearing scale and manure type. Small-scale insect rearing resulted in higher N, P, and K (> 49%) as well as higher Zn (> 59%) and Fe (>27%) reductions. Large-scale insect rearing resulted in higher fiber reduction (6-42%). Abstract : Data from this study demonstrates that manure type and scale impact the ability of the black soldier fly and house fly larvae to biodegrade manure.